De cuando Pinocho aprende valores. Una lectura de la novela de Collodi a la luz de las teorías de Shalom H. Schwartz y Leonardo Boff - Rubio Torres, Carlos (2009)
Carlo Collodi published the chapters of the story Pinocchio in a children’s newspaper between 1880 and 1883. Since that time, Pinocchio has become universally known as a fundamental work in literature. Based on the perspectives of social psychologist Shalom H. Schwartaz and theologian Leonardo Boff, the author of this article contemplates the possibility that Pinocchio’s story allows the reader to develop greater social and moral values for living.